Suburban governance : a global view - Hamel, Pierre, 1947-; Keil, Roger, 1957- (Global suburbanisms., 2015)
Suburban Governance: A Global View is a groundbreaking set of essays by leading urban scholars that assess how governance regulates the creation of the world's suburban spaces and everyday life within them.